Supraventricular Tachycardia, Types and Immediate Management; Experience at a Tertiary Care Hospital of South Punjab - Farhan Ul Haq, Muhammad Younas, Tauseef Asma Chaudhry, Rubina Tousif, Baqir Maqbool, Rana Umar Ayub, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: The objective of this study was to determine efficacy of different optimal adenosine doses in children presenting with supraventricular tachycardia (SVT) at a tertiary care hospital. Methods: A descriptive case series design was undertaken at the Department of Cardiology at the Chaudhry Pervez Elahi Institute of Cardiology in Multan between June 2021 and June 2022. Both genders, age groups less than 14 years, and patients with SVT. The data collection procedure involved the use of a specialized proforma to record the findings of the study. Adenosine was quickly dispensed in escalating doses of 100, 200, and 300 μg/kg. The reaction was captured using a 12-lead ECG, and instances of pre-excitation were noted. The success of the therapy was assessed by identifying a sustained sinus rhythm for a period exceeding three minutes as a positive outcome. Results: A total of 71 participants were included in the study. Out of these, 55 (77.5%) were males. 33.8% presented with a predisposing factor. The most common predisposing factor was LRTI and diarrhea in 47 (66.2%) patients. As per our findings, out of 71 patients who were administered 100 ug per kg of adenosine for SVT, 27 (38.0%) while the remaining refractory 42 patients were administered 200 ug per kg of adenosine. Out of these 42, 26 (61.9%) reverted back to sinus rhythm i.e. 200 ug per kg dose of adenosine was effective in 61.9% cases of SVT. The remaining patients reverted back at 300 ug per kg dose of adenosine. Conclusion: A higher dose of 200 ug per kg was effective in 61.9% of cases. This indicates that a higher dose of adenosine is more effective in treating SVT in children. Additionally, the study found that LRTI and diarrhea were the most common predisposing factors for SVT in children. These findings can be useful in improving the management of SVT in children, especially when considering the optimal dose of adenosine for treatment. Keywords: Adenosine, Supraventricular tachycardia, Pediatric cardiology, Dose optimization, Predisposing factors Sinus rhythm